Techno-Economic Approach for the Analysis of Uniform Horizontal Shading on Photovoltaic Modules: A Comparative Study of Five Solar Sites in Mauritania - Mrabih Rabou, Cheikh Malainine; Yahya, Ahmed Mohamed; Samb, Mamadou Lamine; Yetilmezsoy, Kaan; Rehman, Shafqur; Menezo, Christophe; Mahmoud, Abdel Kader (MDPI, 2026)
Photovoltaic (PV) performance in desert environments is significantly hindered by soiling and partial shading. To bridge the gap in empirical data for extreme Saharan conditions, this study presents a novel techno-economic assessment of uniform horizontal shading (UHS) specifically conducted in Mauritania. Controlled outdoor experiments were performed using a 250 W crystalline silicon PV module and a PVPM 2540C I-V curve tracer, applying progressive shading levels from 2.5% to 20%. The novelty of this work lies in the integration of high-resolution experimental I-V/P-V characterization with a localized techno-economic model for five pre-commercial PV plants. It was observed that PV modules are exceptionally sensitive to shading; specifically, a mere 10% shaded area leads to a catastrophic 90% drop in power and current, while the voltage remains remarkably stable. Thermographic analysis further validates the thermal gradients and bypass diode functionality. By quantifying the financial impacts, this research highlights that cumulative economic losses across the five real-world sites reached 87.95%, exceeding 55,000 MRU. These findings provide a strategic framework for optimizing PV systems in arid terrains and offer a robust tool for enhancing the design and operation of large-scale solar applications in desert environments.
Keywords: photovoltaic modules; uniform shading; techno-economic analysis; PV performance degradation; thermographic inspection; desert climate; Mauritania; POWER POINT TRACKING; PV MODULES; PERFORMANCE; ARRAY; VALIDATION; SYSTEMS; PANELS; DUST; Energy & Fuels